Penyuluhan Standar Produksi Ayam Petelur Jantan pada Kelompok Ternak Nawawi Farm - Mira Andriani; Reikha Rahmasari; Shokhirul Imam; Niati Ningsih; Aryanti Candra Dewi (Journal of Community Development, 2020)
One of the livestock groups engaged in raising male laying hens is the "Nawawi Farm" Farmer Group, which is located in Nogosari Village, Jember Regency. This group is chaired by Mr. Ainul and consists of approximately 100 breeders. Based on discussions with members of the livestock group, breeders have several problems. Farmers experience a lack of standard information on feed nutrient requirements, feed amount and feed conversion. The unknown standard of feed nutrient in male layer hens causes breeders to find it difficult to achieve the target harvest. Therefore, it is necessary to provide counseling on the production standards of male layer hens in the "Nawawi Farm" livestock group. The method of implementing the activity is in the form of a Focus Group Discussion (FGD) with stages, namely the analysis of community needs, counseling on the production standards of male laying hens, and guiding the maintenance of male laying hens. The output of this dedication is that all breeders of the "Nawawi Farm" livestock group can understand the production standards of male laying hens. Rations with protein, namely 18% crude protein, had no effect on feed consumption, FCR, mortality, production index. Rations with 18% crude protein can replace rations with 21% crude protein for feeding male layer hens. This service activity was welcomed by all breeders from the "Nawawi Farm" livestock group so that the service that has been carried out is well organized. Suggestions from this activity are expected that this service will be held at the next meeting in the form of competency training for making rations with the use of local materials in meeting the nutrient feed standards in raising male layer chickens in the "Nawawi Farm" livestock group of Jember Regency, in order to increase the production standards of male layer chickens so that they get greater profit.